Domestic Philosophy of Law as an Ideological Prerequisite of a Philosophical Type of Understanding of Law - Vladimir Valentinovich Kozhevnikov; Anastasia Evgenievna Cherednichenko (Budapest International Research and Critics University, 2019)
This scientific article is based on the analysis of some, from our point of view, basic provisions of the textbook for masters by the famous Russian scientist, professor Martysciin Orestes Vladimirovich